2019
DOI: 10.1002/jcb.29231
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐140 inhibit prostate cancer cell invasion and migration by targeting YES proto‐oncogene 1

Abstract: Prostate cancer (PCa), which is an aggressive malignancy of the male genitourinary system. In the present study, the effects of microRNA‐140 (miR‐140) on PCa were determined. We transfected miR‐140 mimics or negative control into PCa cells, and we used MTT, wound healing, and Transwell assays for determining the capacities of miR‐140 in cell proliferation, migration, and invasion, respectively. We also confirmed the relationship between miR‐140 and YES proto‐oncogene 1 (YES1) using Luciferase reporter assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In harmony with an oncogenic role of YES1, several microRNAs have been shown to inhibit the proliferation of tumor cells by targeting YES1 (Tan, Lim and Tan, 2015, Shen et al, 2019, Zhao et al, 2020.…”
Section: Several Lines Of Evidence Have Established An Oncogenic Rolementioning
confidence: 99%
“…In harmony with an oncogenic role of YES1, several microRNAs have been shown to inhibit the proliferation of tumor cells by targeting YES1 (Tan, Lim and Tan, 2015, Shen et al, 2019, Zhao et al, 2020.…”
Section: Several Lines Of Evidence Have Established An Oncogenic Rolementioning
confidence: 99%
“…Zhao et al. reported that miR-140 inhibited PC cells invasion and migration by targeting YES proto-oncogene 1, indicating that miR-140 could be a potential target for PC therapy ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, miRNAs are regarded to be negative regulators of gene expression ( 72 ). Previous studies indicated that miR-140 functions as a tumor suppressor by targeting several kinds of genes, including FEN1 ( 60 ), YES1 ( 62 ) and BIRC6 ( 73 ). Downregulation of miR-140 is implicated in the development of PC by regulating cancer stem cell formation, tumor invasion, and angiogenesis ( 73 , 74 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 MiR-140 overexpression impeded migration and invasion of prostate cancer cell. 25 Moreover, miR-140-5p also has been revealed as a suppressor in gastric cancer, hepatocellular carcinoma, breast cancer, and so forth. [26][27][28] Our study proved that miR-140 overexpression impeded the development of esophageal cancer in vitro and in vivo, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%